Distribution of lymphoma subtypes in Ukraine according to the WHO 2016 classification. Issue 1 (19th August 2022) - Kriachok, Iryna; Stepanishyna, Yana; Skrypets, Tetiana; Shokun, Nazar; Martynchyk, Arina; Tytorenko, Iryna; Aleksik, Olena; Krotevych, Mykhailo; Manni, Martina; Federico, Massimo
Abstract: The Ukrainian Lymphoma Registry (ULR) was established in 2019 with the aim of monitoring the quality of diagnosis, staging, and treatment of lymphoma in Ukraine. Between September 2019 and October 2021, 546 patients with newly diagnosed lymphoma were prospectively registered. All cases were diagnosed according to the 2016 updated WHO lymphoma classification. The male‐to‐female ratio (M/F) for the whole population was 0.7, with a median age of 46 years (range 18–95). The adoption of the 2016 WHO classification resulted in the identification of 36 different lymphoma subtypes, with 132 cases (24.2%) classified differently compared to the 2008 WHO classification. Only 12 cases (2.8%) were true new entities, including seven cases of high‐grade B‐cell lymphoma NOS, three of anaplastic large B‐cell lymphoma, ALK‐negative, 1 case of HHV8+ DLBCL NOS, and 1 of high‐grade B‐cell lymphoma with C‐MYC and BCL2/BCL6 rearrangement. Moreover, 55 (61.1%) entities, including 37 defined by WHO 2008 and 18 defined by WHO 2016, were not represented at all. The analysis of cases registered in the ULR provides a comprehensive breakdown of the subtypes, stage distribution, and treatment of malignant lymphomas (ML) in Ukraine, supporting the usefulness of prospective data collection and timely reporting. We believe that this study is the first step toward a better understanding of the real‐life outcomes of patients with ML.